The Influence of Linguistic Intellegence Level and Reading Interest on Narrative Writing Skills of Students in Fifth Grade Primary School - Nur Patmawati; Sulfasyah Sulfasyah; Muhammad Akhir (Edumaspul: Jurnal Pendidikan, 2022)
The influence of the level of linguistic intelligence and reading interest on the narrative writing skills of fifth-grade students. This study uses a quantitative explanation with an ex post facto research model with a total sample of 40 students. The results of this study indicate that: (1) The level of linguistic intelligence obtained an average score of 87.38, and the distribution of scores of 40 students (100%) was in the medium category. (2) Students' reading interest obtained an average score of 89.93, and the distribution of scores, as many as 38 students (95%) were in the very good category, and two students (5%) were in a good category. (3) The average score of students' narrative writing skills was 35 students (87.5%) in the very good category, while five students (12.5%) were in the good category. (4) There is no significant effect of the level of linguistic intelligence on students' narrative writing skills. (5) There is a direct influence between reading interest on students' narrative writing skills. (6) There is a positive and significant influence between the level of linguistic intelligence and reading interest on students' narrative writing skills.